THEORETICAL ASPECTS OF USING MODERN TOOLS, TECHNOLOGIES AND METHODS OF CREATIVE MANAGEMENT IN MANAGEMENT INNOVATIONS - HRABOVSKA Іryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the study of the article is devoted to the study of strategic advantages for enterprises and organizations from the development of management innovations, in particular, creative management methods. The urgent need to research the creativity and innovativeness of enterprise management systems for the purpose of their further development has been revealed. The main problems on the way to increase the level of innovative activity of enterprises due to the introduction of creative management innovations were studied, their features and main types were considered. The interrelationship, functional interdependence of the creative management system and creative components of preparation and management decision-making have been revealed. The place and role of creative management systems as a tool for the development and implementation of non-standard management solutions at enterprises in conditions of uncertainty, as well as the key problems of the introduction of management innovations, are revealed. The article points out the need for additional research in order to form a theoretical basis for determining the main trends in the transformation of the managerial functional activity of the organization and the characteristics of the modern stage of development of the innovation management system. The content of the stages of the process of finding creative solutions based on the introduction of modern tools, technologies and methods of creative management into the practice of managing domestic enterprises is highlighted and considered. The characteristics of the roles of creative workers who directly participate in innovation processes are given. Particular attention in the article is devoted to the features, principles and innovative methods of creative management. The study noted an increase in the application of idea generation methods - from the use by individuals to building up the intellectual capital of the organization with the help of regular trainings.